Monitoring the Absorption Dose of X-ray Radiation on the Thoracic Examination - Hadinata, I Made Hendra; Rupiasih, Ni Nyoman (BULETIN FISIKA; Vol 21 No 1 (2020): BULETIN FISIKA, 2020)
The study of monitoring the absorption dose of X-ray radiation received by thoracic examination patients has been conducted. The absorbance dose received by the patient is calculated from the exposure factor data consisting of electric voltage (kV), current (mA), time (s), and examination distance (m). Data were obtained from 130 male patients and 60 female patients, who performed thoracic examinations in a Posterior Anterior (PA) position. The absorbed dose received by male and female patients is compared with the maximum absorbed dose determined by BAPETEN for thoracic examinations on adult patients, which is 0.4 mGy. Differences in the absorbed dose received by male and female patients were identified by the T-test of two free samples with a significance level of 0.05. The results showed that the dose of X-ray radiation received by male and female patients was still below the maximum absorbed dose determined by BAPETEN, and the results of the T-test showed no significant difference in the absorbed dose received by male and female patients.